Recovery of vegetation and bees after removal of pine forests by fire in the Limietberg region of the Cape Floristic Region biodiversity hotspot - Gardee, Muhammed Nizaar (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.